Titanic - Dubowski, Mark; Nang ChanYeema (New York, USA DK Publishing Inc., 1998)
Describes, in easy-to-read text, the disastrous 1912 sinking of the world's largest ocean liner after colliding with an iceberg during its maiden voyage.
Keywords: Level Books